Comparative GC Analysis of Seed Essential Oils from Tunisian and German Caraway ( Carum carvi L.) Ecotypes - Laribi, Bochra; Kouki, Karima; Bettaieb, Taoufik; Mougou, Abdelaziz; Marzouk, Brahim (Pharmacognosy Communications)
Background: Caraway ( Carum carvi L.) seeds have been used numerously throughout history as a condiment and for its medicinal properties. Objective: The present study aims to compare the Tunisian and German caraway ecotypes regarding their seed essential oil compositions. Materials and Methods: Seed essential oil composition of two caraway ecotypes from Tunisia and Germany, cultivated under the same pedoclimatic and cultural conditions has been analysed by gas chromatography (GC) and gas chromatography-mass spectrometry (GC-MS). Results: The essential oil yields differed signifi cantly between the two caraway ecotypes: 1.41% and 0.48% for Tunisian and German seeds, respectively. Forty one (41) volatile compounds were identifi ed in the two oil samples where carvone and limonene constituted the main components but with signifi cantly different proportions. Consequently, the two caraway ecotypes displayed the same chemotype, namely carvone. Additionally, the proportions of some minor essential oil compounds such as ketones, oxygenated monoterpenes and sesquiterpenes were found to be signifi cantly different between the German caraway seed essential oil and the Tunisian one. Conclusion: Since the infl uence of different environmental factors has been eliminated, the observed differences in seed essential oil yield and composition between the two studied ecotypes seem likely to result from the genetic variability
Keywords: Carum carvi L .; seeds; essential oil; carvone; limonene